Ciclo de vida da área turística: o caso do pontal de Coruripe-AL - Silva, Priscylla Maria Ferreira da (2016)
This study examines the tourism area life cycle of the village of Pontal de Coruripe, Alagoas state, Brazil. The model of the tourism area life cycle (TALC) (BUTLER, 1980) has been widely used over more than thirty years to study destinations, places and attractions around the world; the model seeks to understand the local contextual characteristics of destinations since the destination inception to the present. Pontal de Coruripe, which is located in the municipality of Coruripe, just as most of the Alagoas’ littoral has a territory that is marked by the influence of tourism with a history of accommodation building commencing in the 1980s. The study seeks to understand how and when Pontal e Coruripe emerged as a tourist place, how it developed over time up to the present, and which were the main factors influencing its evolution. The work uses an exploratory case study which was developed by means of a qualitative research approach. A TALC study involves mainly a characterization of the temporal evolution of a place’s accommodation sector, based on the number of hotel rooms; in this study it also sought to identify and analyze the influences that the accommodation sector and visitors have exerted on the local territory over time. The main data colleting instrument used was a semi-structured interview which was run with the owners or managers of current or previous local accommodation units of Pontal de Coruripe. The interviews were recorded and transcribed and were analyzed using the content analysis method. The study shows that second-homes represented the kick-off of the touristification process in Pontal de Coruripe which was later followed by the opening of commercial accommodation units. Three decades after the opening of the first accommodation units the destination shows the emergence of Butler’s (1980) decline stage; the destination also shows a history of lack of integration between local tourism agents.